Digital Printing of Textiles - Ujiie, H (Woodhead publishing in textiles, 2006)
This comprehensive introduction to the textile industry is broken into five sections. After two introductory chapters, it goes on to look in a number of detailed chapters at printer and print head technologies. The next section examines the printer software required for successful color design and management. The digital printing coloration process is explored next, with chapters on substrate preparation, pigmented ink, aqueous inkjet ink, pre-treatment and printing on cationized cotton with reactive inks. The book is concluded with three chapters on the design and business aspect of digital printing.